Accumulation of 99mTc-Cysteine in Experimental Inflammatory Lesions in Comparison to 99mTc-Glutamine and 99mTc-HIG - Ercan, M. T.; Gülaldi, N. C. M.; Uysal, U.; Ünsal, S.; Aydin, M.; Peksoy, İ.; Hasçelik, Z. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: The aim of this experimental work was to investigate the efficacy of 99mTc-L-Cysteine (Cys) in scintigraphic visualization of inflammatory lesions in comparison to 99mTc-L-glutamine (G), and 99mTc-HIG. Methods: In mice abscesses were induced by intramuscular injection of turpentine. Six days later mice were injected with 3.7 MBq of each agent and sacrificed in groups of three at 1, 3, 6 and 24 h. Scintigrams were obtained with a gamma camera. The organs, some blood, abscesses, some muscle and urine were removed, weighed and counted in a gamma counter. Percentage of uptake by organs and per gram tissues and abscess/normal tissue concentration ratios were calculated. Experimental arthritis was produced in 6 New Zealand rabbits by intraarticular injection of ovalbumin. Four days later 37 MBq of 99mTc-Cys and 99mTc-HIG were each i.v. administered to 3 rabbits. Scintigrams obtained at 1, 3, 6, and 24 h demonstrated the arthritic joints very well. ROI’s over arthritic joints were compared to contralateral normal joints (A/C). Results: In mice the abscesses were well visualized on all scintigrams. The maximum abscess/muscle ratios were 5.21 ±1.09 (6 h), 3.73 ± 0.81 (3 h) and 5.98 ± 1.17 (24 h) and the maximum abscess/blood ratios were 3.46 ± 1.33 (24 h), 1.81 ± 0.10 (6 h) and 0.914 ± 0.351 (24 h) for 99mTc-Cys, 99mTc-G, and 99mTc-HIG, respectively. In rabbits the maximum A/C ratios were 2.61 ± 0.53 (3 h) and 2.92 ± 0.99 (24 h) for 99mTc-Cys and 99mTc-HIG, respectively. Conclusion: our results indicate that 99mTc-Cys is a promising agent for imaging inflammatory lesions. It is preferred to 99mTc-HIG, because of higher concentration ratios attained earlier, lower blood background, lower cost and a simpler in-house preparation method.
Keywords: 99mTc-Cysteine; 99mTc-Glutamine; 99mTc-HIG; abscess; arthritis